Genetic analysis and association of simple sequence repeat markers with storage root yield, dry matter, starch and β-carotene content in sweetpotato - Yada, B.; Brown-Guedira, Gina; Alajo, A.; Ssemakula, G.N.; Owusu-Mensah, E.; Carey, E.E.; Mwanga, Robert O.M.; Yencho, George Craig (Japanese Society of Breeding, 2017)
Molecular markers are needed for enhancing the development of elite sweetpotato (Ipomoea batatas (L.) Lam) cultivars with a wide range of commercially important traits in sub-Saharan Africa. This study was conducted to estimate the heritability and determine trait correlations of storage root yield, dry matter, starch and <beta>-carotene content in a cross between ‘New Kawogo’ x ‘Beauregard’. The study was also conducted to identify simple sequence repeat (SSR) markers associated with these traits. A total of 287 progeny and the parents were evaluated for two seasons at three sites in Uganda and genotyped with 250 SSR markers. Broad sense heritability (H2) for storage root yield, dry matter, starch and <beta>-carotene content were 0.24, 0.68, 0.70 and 0.90, respectively. Storage root <beta>-carotene content was negatively correlated with dry matter (r = -0.59, P < 0.001) and starch (r = -0.93, P < 0.001) content, while storage root yield was positively correlated with dry matter (r = 0.57, P = 0.029) and starch (r = 0.41, P = 0.008) content. Through logistic regression, a total of 12, 4, 6 and 8 SSR markers were associated with storage root yield, dry matter, starch and <beta>-carotene content, respectively. The SSR markers used in this study may be useful for quantitative trait loci analysis and selection for these traits in future.